The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.3141/1737-08
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration Characteristics of Starting Vehicles

Abstract: Acceleration characteristics of starting vehicles are needed for many transportation analysis and design purposes involving driveways, turning bays, intersecting streets, traffic signals, railroad crossings, simulation software, etc. Constant acceleration is sometimes assumed or AASHTO Green Book values based on piecewise-constant accelerations are sometimes adopted. Yet, continuing research has shown linearly-decreasing acceleration rates better represent both maximum vehicle acceleration capabilities as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 2 publications
1
65
0
8
Order By: Relevance
“…In this way, the speed transitions can represent acceleration, deceleration or a constant speed stage. The acceleration and deceleration curves of the vehicles can be defined in different ways [44,45]. For simplicity, constant acceleration, depending on the gear engaged, is considered for speed transitions of the vehicle, according to [39].…”
Section: Optimization Data Setmentioning
confidence: 99%
“…In this way, the speed transitions can represent acceleration, deceleration or a constant speed stage. The acceleration and deceleration curves of the vehicles can be defined in different ways [44,45]. For simplicity, constant acceleration, depending on the gear engaged, is considered for speed transitions of the vehicle, according to [39].…”
Section: Optimization Data Setmentioning
confidence: 99%
“…On our own data, obtained using a family sedan and a van, we observed maximum deceleration to be under 1.5m/s 2 . The maximum rate of acceleration of a normal road vehicle is significantly lower than the maximum rate of deceleration [30]; therefore, we will assume acceleration in normal circumstances to be under 1.5 m/s 2 as well.…”
Section: Feature Matchingmentioning
confidence: 99%
“…On the other hand, Wang et al (2004) have assumed that drivers normally accelerate with a polynomial decreasing relationship with speed. Long (2000) has concluded that linearly decreasing acceleration rates better represent both maximum vehicle acceleration capabilities and actual motorist behaviour.…”
Section: Signalised Traffic Flow At Intersectionmentioning
confidence: 99%
“…Currently, constant acceleration is assumed by most simulation packages. However, Long (2000) has shown that linearly decreasing acceleration rates better represent both maximum vehicle acceleration capabilities and actual motorist behaviour. For the headway problem, Jin et al (2009) have found that the distributions of the departure headways at each position in a queue are shown to approximately follow a log-normal distribution and the corresponding mean values level out gradually.…”
Section: Case-studiesmentioning
confidence: 99%
See 1 more Smart Citation